2004
DOI: 10.1021/jf049607f
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Analysis of Carotenoid Biosynthesis in Flavedo of Orange (Citrus sinensis L.) during Fruit Development and Maturation

Abstract: Changes in carotenoid content and composition and expression of carotenoid biosynthetic genes were analyzed in the flavedo of sweet orange (Citrus sinensis L. Osbeck, cv. Navelate) fruit during development and maturation. Lutein and all-E-violaxanthin were the major carotenoids in chloroplast-containing tissues. During fruit coloration, phytoene, beta-cryptoxanthin, zeaxanthin, and mainly (9Z)-violaxanthin progressively accumulated, and a large proportion of apocarotenoids was also found in the flavedo of full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
195
1
25

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(233 citation statements)
references
References 35 publications
(57 reference statements)
10
195
1
25
Order By: Relevance
“…[29]. In addition, the color was well described by a*/b* ratio which was negative for green fruits, zero for yellow fruits, and positive for orange fruits [30]. Alternatively, the color also could be depicted by H° as follows: 0° for reddish-purple, 90° for yellow, 180° for bluish-green and 270° for blue [31,32].…”
Section: Discussion:-mentioning
confidence: 99%
“…[29]. In addition, the color was well described by a*/b* ratio which was negative for green fruits, zero for yellow fruits, and positive for orange fruits [30]. Alternatively, the color also could be depicted by H° as follows: 0° for reddish-purple, 90° for yellow, 180° for bluish-green and 270° for blue [31,32].…”
Section: Discussion:-mentioning
confidence: 99%
“…For example, it has been shown that chlorophyllase, a constitutively expressed gene, does not increase during natural fruit development (JacobWilk et al, 1999). In addition, the expression patterns of carotenoid biosynthetic genes and an associated abundance of carotenoids during ripening have recently been reported (Kato et al, 2004;Rodrigo et al, 2004;Alós et al, 2006). It is noteworthy that citrus peel contains the greatest diversity of carotenoids of any fruit studied to date and their specific accumulation patterns are responsible for the broad range of colors exhibited by PHYSIOLOGY OF CITRUS FRUITING citrus fruits (Gross, 1987).…”
Section: External Ripeningmentioning
confidence: 99%
“…It has also been reported that ABA synthesized in vegetative tissues is translocated to the seeds. The distribution of ABA is an important factor in determining the endogenous concentrations of the hormone at the site of action, and hence, it is an important process in physiological responses (14). It is now well established that ABA in plants is synthesized from carotenoids (C40) and is an apo-carotenoid compound derived from oxidative cleavage of the 11,12 double bonds of 9-cisepoxycarotenoids (18).…”
Section: Introductionmentioning
confidence: 99%